Tailoring laser-induced domain wall pinning - Möhrke, Philipp; Rhensius, Jan; Thiele, Jan-Ulrich; Heyderman, Laura; Kläui, Mathias (My University, 2010)
Field-induced domain wall (DW) motion in Permalloy microwires under the influence of thermal gradients is studied using magneto-optical Kerr-microscopy. The DW is found to be pinned at two positions in a laser spot focused onto the wire. By tuning the laser power, the pinning strength can be engineered. On increasing the laser power, the depinning field for the first pinning site in the first half of the laser spot is found to decrease, while for the second pinning site in the spot region located beyond the centre of the spot it increases. Below a threshold power WT, the pinning strength can be tuned reversibly while above WT irreversible increases in the pinning strength due to structural changes occur. This effect can be employed for flexible pinning sites for DW devices.
Keywords: Nanostructures; Spin dynamics; Light absorbtion and reflection; 530